One hundred years making science: the Chair of Medical Hydrology in the Faculty of Medicine, Complutense University (1912-2012). Exhibition catalog - Rodríguez Sánchez, Juan Antonio; de Jorge García-Reyes, Javier; Crego Castaño, Manuela (Anales de Hidrología Médica, 2013)
On the occasion of the first century’s anniversary of the creation of the Chair of Medical Hydrology in the Central University (now so-called University Complutense of Madrid) was organized at the Faculty of Medicine, from April to June 2012, an exhibition of books, handwritten memories, administrative documents, drawings, photographs and objects that allow displaying the circumstances surrounding the creation of this chair, its evolution and main contributions, as well as its present and future challenges. Physical exposure is accompanied by an expanded virtual version that guarantees permanent access and the addition of new documents.
Keywords: Medical Hidrology; Exhibitions; Bibliography